A checklist of the oribatid mite species (Acari, Oribatida) of Ethiopia - Ermilov, Sergey G.; Rybalov, Leonid B. (Zootaxa, 2026)
A checklist of oribatid mites (Oribatida) registered in Ethiopia is presented, based on published literature from 1916 to 2025. It includes the names of species, their general known distribution, distribution by regions and habitat in Ethiopia, and references. A total of 375 species/subspecies, belonging to 165 genera, 72 families, 32 superfamilies, and five infraorders, is given. The proportion of Brachypylina is 311 species/subspecies (83%). Most of the species/subspecies (337) were recorded for the first time in the Ethiopian fauna in 2010–2025. Among oribatid species, 121 species are known only from Ethiopia, 150 species are Afrotropical, and 104 species have a wider distribution. Many species were found in litter-soil in various forest associations. Considering that there is no significant knowledge for some Ethiopian regions and habitats, a large number of new species and distribution/habitat records could be discovered in the future.